Factores contribuyentes a la deshumanización del personal de enfermería de terapia intensiva - Villalva Guevara, Evelyn Gianelia (2025)
The lack of values in nursing care increases significantly with time and with the level of expertise acquired in the intensive care area, thus leading to dehumanization, lack of empathy and lack of interaction with users and relatives, which is reflected negatively in the procedures that are routinely performed. Therefore, the aim of the research was to identify the factors contributing to the dehumanization of Intensive Care nurses. A predominantly qualitative approach was applied to the research, which included scientific articles that were indexed in databases such as PubMed, Scielo, Dialnet and Google. However, articles from journals that were not indexed, as well as undergraduate theses, were excluded from the review process. As a result of the research, it became evident that several authors agreed that the main factors of dehumanization are the increasing technification of care with biomedical equipment and during the literature review, it was concluded that the dehumanization of professional nursing staff in their practice reflects dehumanization traits associated with various factors that distance the professional from respectful care with values, turning it into routine.